2015
DOI: 10.5194/asr-12-11-2015
|View full text |Cite
|
Sign up to set email alerts
|

Wind variability in a coastal area (Alfacs Bay, Ebro River delta)

Abstract: Abstract. Wind spatial heterogeneity in a coastal area (Alfacs Bay, northwestern Mediterranean Sea) is described using a set of observations and modelling results. Observations in three meteorological stations (during 2012-2013) along the coastline reveal that wind from the N-NW (strongest winds in the region) appears to be affected by the local orography promoting high wind variability on relatively short spatial scales (of the order of few kilometres). On the other hand, sea breezes in late spring and summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 22 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…A channelisation effect associated with the Ebro valley triggers north-westerly winds (called Mestral: Catalan for Mistral wind), resulting in a wind jet. Previous studies based on long-term wind measurements in the proximity of the region showed that winds have a persistent seasonal pattern (Font, 1990;Cerralbo et al, 2015;Grifoll et al, 2015). During winter and autumn, a dominant northwesterly component caused by wind channelisation was observed.…”
Section: Study Area and Observationsmentioning
confidence: 88%
See 1 more Smart Citation
“…A channelisation effect associated with the Ebro valley triggers north-westerly winds (called Mestral: Catalan for Mistral wind), resulting in a wind jet. Previous studies based on long-term wind measurements in the proximity of the region showed that winds have a persistent seasonal pattern (Font, 1990;Cerralbo et al, 2015;Grifoll et al, 2015). During winter and autumn, a dominant northwesterly component caused by wind channelisation was observed.…”
Section: Study Area and Observationsmentioning
confidence: 88%
“…The westerly wind, greatly affected by the orography, is channelised into a limited band, forming a wind jet (Jansà, 1985;Spanish Ministry of Energy, 2014). The synoptic situation is related to an anticyclone in the Bay of Biscay and a low-pressure area in the Mediterranean Sea (Riosalido et al, 1986;Font, 1990;Martín-Vide, and Olcina, 2001;Cerralbo et al, 2015). Offshore wind is more usual and intense during autumn and winter, when larger atmospheric pressure gradients take place and cause stronger winds with an advection of cold air, but a small atmospheric pressure difference along the Ebro valley is sufficient to initiate wind during any season (Riosalido et al, 1986;Cerralbo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that other processes entirely mask the linear response, assuming a linear behavior as an expected direct response of the water current at wind forcing. It means that the hydrodynamic response is conditioned by nonlinear and non-stationary processes due to the intricate bathymetry, the unsteadiness of the wind magnitude and direction and probably the spatial wind heterogeneity in the bay (Cerralbo et al, 2015). Aside Alfacs Bay, this behavior is common in highly-stratified and shallow estuaries where the correlation with wind events is complex and nonlinear (Noble et al 1996, Narváez and.…”
Section: Hydrodynamic Responsementioning
confidence: 99%
“…The three-dimensional hydrodynamic model used in this study is the Regional Ocean Modeling The skill assessment of the atmospheric model was presented previously in Cerralbo et al (2015b).…”
mentioning
confidence: 99%